2014
DOI: 10.5935/0103-1104.2014s025
|View full text |Cite
|
Sign up to set email alerts
|

Condições sensíveis à atenção primária: uma revisão descritiva dos resultados da produção acadêmica brasileira

Abstract: RESUMO O estudo propõe-se descrever e analisar os resultados da produção acadêmica brasileira sobre Internações por Condições Sensíveis à Atenção Primária. Revisão descritiva e analítica realizada em artigos científicos de Portais de Periódicos. Vinte e um artigos integraram o estudo, os quais foram subdivididos segundo a abrangência territorial, sendo 9,6% nacional, 4,8% do Nordeste, 9,6% do Centro-Oeste, 33,3% do Sul e 42,7% do Sudeste. As Internações por Causas Sensíveis à Atenção Primária, apesar de se apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
1
12
0
16
Order By: Relevance
“…10,18,25,26 According to the national literature, the most prevalent diseases among children aged 0-4 years in the Southeast are infectious gastroenteritis and its complications and bacterial pneumonia. 9,26 A study in Piauí of the 1 -4 year age group, between 2000 and 2010 found the main causes to be related to infectious and parasitic diseases, respiratory disorders and diseases of the digestive tract in that order. 12 An international study found the six main diagnoses in a population aged under 18 years to be asthma, dehydration/gastroenteritis, pneumonia, convulsions, skin infection, and infection of the urinary tract, which accounted for 90% of hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,18,25,26 According to the national literature, the most prevalent diseases among children aged 0-4 years in the Southeast are infectious gastroenteritis and its complications and bacterial pneumonia. 9,26 A study in Piauí of the 1 -4 year age group, between 2000 and 2010 found the main causes to be related to infectious and parasitic diseases, respiratory disorders and diseases of the digestive tract in that order. 12 An international study found the six main diagnoses in a population aged under 18 years to be asthma, dehydration/gastroenteritis, pneumonia, convulsions, skin infection, and infection of the urinary tract, which accounted for 90% of hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…9 There are few studies that address pediatrics and adolescents. [10][11][12] Studies of this age group are important since, different from adults, acute conditions predominate in this sector of the population.…”
Section: Introductionmentioning
confidence: 99%
“…O declínio dos valores desse indicador de qualidade de assistência à saúde com foco na atenção primária acompanha os estudos realizados no Brasil e no mundo, além de sugerir que a lista brasileira contém condições que de fato podem ser tratadas nesse nível de atenção, prevenindo agravos que geram internações [12][13][14][15][16] . Destaca-se, nessa direção, a redução de 38,1% na cidade de Florianópolis em um período um pouco menor, de 2005 a 2011, no qual ocorreu o mesmo movimento de expansão da APS, indo de 61,7 a 89,3% de cobertura de ESF no período analisado e chegando a 100% de cobertura no ano de 2015 16 .…”
Section: ▄ Discussãounclassified
“…196;BRASIL, 1988). explicações para tais ocorrências, muitas vezes associadas à deficiência na cobertura dos serviços ou baixa resolutividade da atenção primária para algumas patologias(ALFRADIQUE et al, 2009;PEREIRA et al 2014). Nesse aspecto, o olhar desse estudo será direcionado ao Nordeste brasileiro, região que possui o maior quantitativo de estados do País: Maranhão, Piauí, Bahia, Ceará, Rio Grande do Norte, Paraíba, Pernambuco, Alagoas e Sergipe e apresenta, em comparação com as regiões do país, menor Produto Interno Bruto (PIB) per capita, além de maiores taxas de analfabetismo, menores coberturas de esgotamento sanitário e maiores taxas de mortalidade infantil, variáveis importantes na ocorrência de maiores taxas de ICSAP (MOURA et al, 2010).…”
unclassified